Деякі аспекти методики аналізу сучасної музики - Сюта, Б. (Студії мистецтвознавчі, 2008)
The violated in this article problem of the analysis of the modern music, complicated through the permanent growth of action of music outside factors of the modern music creation and its text transformations and anomalies, complications of communicative nature, is extraordinarily important in a scientifically-methodical plan. All these factors are in dissoluble communication, and it is therefore needed permanent and intent attention from the side of tutor, which forms the pupil's ability to correctly select strategy, tactics and tools of the analytical work.